(untitled) (SAARC Journal of Agriculture, 2017)
The imports of edible oils and oilseeds are increasing year after year to fulfill the increasing demand of Bangladesh. Appropriate policy measures are needed to increase oilseed production. Therefore, an in-depth investigation was carried out to assess the challenges and opportunities in the oilseeds sector of Bangladesh. The study analyzes data generated from a sample of 1980 households spread over 11 oilseed growing districts. In addition, eleven focus group discussions (FGDs) were also conducted. The study shows that there are ample opportunities to increase both area and productivity of oilseeds because of availability of short-duration improved varieties and suitable agro-climatic conditions. Also at the production and post-harvest processing levels, there is some potential for mechanical interventions that might add to the current oilseed production processes, and allow farmers to earn more from oilseed cultivation. There are also challenges such as climate variability, competition with other crops for scarce resources, and high infestation of insects & diseases. SAARC J. Agri., 15(1): 161-172 (2017)